Disharmoni Regulasi Agraria dan Kelautan sebagai Penghambat Kepastian Hukum HGB di Wilayah Pesisir Laut: Tinjauan Normatif di Indonesia - Sari, Masda Agatha (Fakultas Hukum Universitas Airlangga, 2025)
This study aims to analyze the disharmony between agrarian law and maritime law in the context of granting Building Rights Title (Hak Guna Bangunan or HGB) in coastal areas, as well as its implications for legal certainty, coastal communities, and the state. The research employs a normative legal method using both statute and conceptual approaches. Primary legal materials consist of relevant legislation, such as the Basic Agrarian Law (UUPA) and the Coastal and Small Islands Management Law (UU PWP3K), along with Constitutional Court decisions. Secondary legal materials, including academic literature, journal articles, and legal doctrines, are also examined. The findings reveal a fundamental inconsistency between agrarian law, which allows the granting of HGB over state land including coastal zones, and maritime law, which prohibits privatization of coastal waters to safeguard public interest and ecological sustainability. This regulatory disharmony generates legal uncertainty for HGB holders, risks of marginalization for coastal communities, and a legal-political dilemma for the state in balancing investment certainty with environmental protection. Therefore, this research recommends the establishment of a more comprehensive harmonization framework between agrarian and maritime regulations to ensure legal certainty, social justice, and environmental sustainability in coastal areas.